Equality of men and women in punishment (study on similarities and differences in punishment) - Muhammad Husni, Ahmad; Muhammad Husni, Amin (Zes Rokman Resources, 2025)
Islam has set punishments between men and women fairly and equitably without burdening, therefore men and women have similarities and differences in terms of Hudud, Qisas and Takzir Punishments. The purpose of this study is to study the similarities and differences between men and women in Hudud, Qisas and Civil Punishments. The method used is a literature study and examining cases involving punishment. As a result of what was studied, the author found differences between men and women in the punishment of stoning for muhsan and ghair muhsan. Next, the punishment in cases of murder and theft, whether the offender is male or female, is punished under the Penal Code. Meanwhile, the punishment for apostasy in Malaysia is set according to the States in Malaysia. Next, the rate of diyat for women is half the diyat for men according to the majority of scholars. Therefore, all of this study is to find out the extent of the similarities and differences between men and women in punishment. The importance of this study is to explain the similarities and differences between men and women in punishment.